Pengaruh Profitabilitas dan Struktur Modal Terhadap Nilai Perusahaan Dengan Moderasi Ukuran Perusahaan - Tristania Putri Aprilia; Riskin Hidayat (Jayapangus Press, 2026)
This study aims to analyze the effect of profitability and capital structure on firm value with firm size as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research used a quantitative associative approach with secondary data obtained from annual financial reports. The sampling technique used purposive sampling and resulted in 80 observation data. Firm value was measured using Price to Book Value (PBV), profitability using Return on Assets (ROA), capital structure using Debt to Equity Ratio (DER), and firm size using the natural logarithm of total assets. Data analysis was conducted using descriptive statistics, classical assumption tests, multiple linear regression, and Moderated Regression Analysis (MRA) with SPSS. The results show that profitability (ROA) has a positive and significant effect on firm value, indicating that companies with higher profitability tend to have higher market value. Capital structure (DER) also has a positive and significant effect on firm value, reflecting that optimal debt utilization can increase investor confidence. Furthermore, firm size is proven to moderate the relationship between profitability and firm value with a weakening effect, meaning that the influence of profitability on firm value is stronger in smaller companies. However, firm size is unable to moderate the relationship between capital structure and firm value. The findings support signal theory and trade-off theory in explaining factors affecting firm value.